التوزع الجغرافي لرخويات الماء العذب في المنطقة الساحلية السورية - فاضل, اقبال (Latakia University Journal -Biological Sciences Series, 2018)
This research includes a list of 38 molluscs species collected during the period 2014-2016 from various stations of the Syrian coastal region (rivers, estuaries, springs, swamps, lakes, pools, reservoirs…). Some of these water bodies are permanent and others are seasonal, some are polluted and others are relatively clean. Among these species, 34 are from Gastropods (20 of Prosobranchia and 14 of Pulmonata) and 4 from Bivalvia. The studied stations were specified and a map showing species distribution in various stations was produced and compared with the global distribution. The number of individuals of each species and their relative frequency were determined. Species were photographed and presented for easy differentiation. After executing the taxonomic and ecological studies, we see that it is necessary to initiate biological studies of these mollusc species. يتضمن هذا البحث قائمة بأسماء 3۸ نوعاً من رخويات الماء جمعت بين الأعوام 2014- 2016 من محطات مختلفة من المنطقة الساحلية السورية (ينابيع ، أنهار ومصبات أنهار، مستنقعات وبرك، بحيرات ذات مصادر مختلفة، خزانات سدود،... )، بعضها دائم الجريان وبعضها الآخر موسمي يتعرض لفترات جفاف، وبعضها خزانات نظيفة نسبياً، وبعضها الآخر يتعرض لملوثات من مصادر مختلفة ومتنوعة، ومن بين هذه الأنواع 34 نوعاً ينتمي إلى صف بطنيات القدم Gastropoda (20 نوع منها من تحت صف أماميات الغلاصم Prosobranchia و14 نوع من تحت صف الرئويات Pulmonata) و4 أنواع من صف ثنائيات المصراع Bivalvia. لقد تم عرض جدول بأسماء المحطات المدروسة، وخريطة تحدد التوزع الجغرافي للأنواع في الأوساط المدروسة المنتشرة في الساحل السوري ومقارنتها مع التوزع العالمي، وتم تقدير عدد الأفراد المجموعة من كل الأنواع المدروسة مع التكرار النسبي ودرجة الثبات لكل نوع ، وتم عرض صور لكافة الأنواع من أجل سهولة تمييزها، ونرى أنه من الضروري التوسع في الدراسات البيولوجية لهذه الرخويات بعد أن تم إنجاز الدراسات التصنيفية والبيئية.ً